Noncomprehensive and Intermittent Obesity‐Related School Programs and Policies May Not Work: Evidence from the COMPASS Study. (30th July 2019) - Laxer, Rachel E.; Dubin, Joel A.; Brownson, Ross C.; Cooke, Martin; Chaurasia, Ashok; Leatherdale, Scott T.
ABSTRACT: BACKGROUND: The school environment has the potential to influence student body mass index (BMI) through programs and policies. Our objective was to examine the effect of modifying obesity‐related school policies and programs on youths' BMI trajectories. METHODS: Obesity‐related school policies and programs related to physical activity and healthy eating were collected from 41 schools across Ontario at baseline (2012‐2013) and year 2 (2013‐2014) of the COMPASS study. Self‐reported height and weight were collected from the 4951 grades 9 and 10 students who attended those schools for 3 years. Linear mixed effects regression models examined the effect of modifying obesity‐related school policies and programs on youths' BMI trajectories. RESULTS: Between Y1 and Y2, 26 of the 41 schools implemented distinct new obesity‐related programs or policies related to physical activity or healthy eating. Five of the interventions were associated with BMI trajectories of students attending those schools compared to students attending a pooled sample of control schools, predicting a higher BMI trajectory. CONCLUSIONS: Isolated programs and policies may not successfully improve youths' BMI trajectories. Further research is required to test the implementation of policies and programs that follow a comprehensive school health (CSH) approach, targeting BMI and associated behaviors.